Regulators of G-protein signalling: multifunctional proteins with impact on signalling in the cardiovascular system - Wieland, Thomas; Mittmann, Clemens (Pharmacology & therapeutics, 2003)
Regulator of G-protein signalling (RGS) proteins form a superfamily of at least 25 proteins, which are highly diverse in structure, expression patterns, and function. They share a 120 amino acid homology domain (RGS domain), which exhibits GTPase accelerating activity for alpha-subunits of heterotrimeric G-proteins, and thus, are negative regulators of G-protein-mediated signalling. Based on the organisation of the Rgs genes, structural similarities, and differences in functions, they can be divided into at least six subfamilies of RGS proteins and three more families of RGS-like proteins. Many of these proteins regulate signalling processes within cells, not only via interaction with G-protein alpha-subunits, but are G-protein-regulated effectors, Gbetagamma scavenger, or scaffolding proteins in signal transduction complexes as well. The expression of at least 16 different RGS proteins in the mammalian or human myocardium have been described. A subgroup of at least eight was detected in a single atrial myocyte. The exact functions of these proteins remain mostly elusive, but RGS proteins such as RGS4 are involved in the regulation of G(i)-protein betagamma-subunit-gated K(+) channels. An up-regulation of RGS4 expression has been consistently found in human heart failure and some animal models. Evidence is increasing that the enhanced RGS4 expression counter-regulates the G(q/11)-induced signalling caused by hypertrophic stimuli. In the vascular system, RGS5 seems to be an important signalling regulator. It is expressed in vascular endothelial cells, but not in cultured smooth muscle cells. Its down-regulation, both in a model of capillary morphogenesis and in an animal model of stroke, render it a candidate gene, which may be involved in the regulation of capillary growth, angiogenesis, and in the pathophysiology of stroke.
Gesehen am 07.04.2022